LEARNING OPENTELEMETRY setting up and operating a modern observability system - Young, Ted; Parker, Austin (O'Reilly Media, Inc., 2024)
OpenTelemetry is a revolution in observability data. Instead of running multiple uncoordinated pipelines, OpenTelemetry provides users with a single integrated stream of data, providing multiple sources of high-quality telemetry data: tracing, metrics, logs, RUM, eBPF, and more. This practical guide shows you how to set up, operate, and troubleshoot the OpenTelemetry observability system. Authors Austin Parker, head of developer relations at Lightstep and OpenTelemetry Community Maintainer, and Ted Young, cofounder of the OpenTelemetry project, cover every OpenTelemetry component, as well as observability best practices for many popular cloud, platform, and data services such as Kubernetes and AWS Lambda. You'll learn how OpenTelemetry enables OSS libraries and services to provide their own native instrumentation--a first in the industry. Ideal for application developers, OSS maintainers, operators and infrastructure teams, and managers and team leaders, this book guides you through: The principles of modern observability All OpenTelemetry components--and how they fit together A practical approach to instrumenting platforms and applications Methods for installing, operating, and troubleshooting an OpenTelemetry-based observability solution Ways to roll out and maintain end-to-end observability across a large organization How to write and maintain consistent, high-quality instrumentation without a lot of work.
Keywords: Amazon Web Services; Cloud computing; Web services; Observers (Control theory); Infonuagique; Services Web; Observabilité (Théorie de la commande)